THE DEVELOPMENT OF TRANSESTERIFICATION PROCESS OF COTTON SEED OIL BY USING MICROWAVE - Andi Suryanto; Zakir Sabara, HW; Andi Artiningsih; Hardi Ismail (Reaktor, 2018)
Biodiesel is a renewable, non-toxic, environmentally friendly fuel made from vegetable oils through a transesterification reaction with methanol. During this time the manufacture of biodiesel takes a long time, which can be overcome with microwave heating. The use of microwave can decrease the reaction time and the amount of catalyst. The purpose of this study was to study the utilization of microwave as a heater in the transesterification reaction of cotton seed oil with the addition of NaOH catalyst 0.25, 0.5, 0.75 and 1% (w/w) with 100 watts microwave power and a reaction time of 15 minutes. Conversion of biodiesel from cotton seed oil with the NaOH catalyst concentrations 0.5% (w/w), 5 minutes, molar ratio of 1: 12 with a microwave power of 400 watts was 99.11%. The results of the analysis of several parameters on biodiesel products show that they have met the specifications based on Indonesian National Standard (SNI-04-7182-2006). Keyword: biodiesel, transesterification, cotton seed oil, microwave.